Contribution to the knowledge of Chinese Phasmatodea III: Catalogue of the phasmids of Hainan Island, China, with descriptions of one new genus, one new species and two new subspecies and proposals of three new combinations - Ho, George Wai-Chun (Zootaxa, 2016)
A catalogue of the phasmids of Hainan Island, China is provided. This study presents 25 genera and 59 species. A new genus, Pseudoparamenexenus gen. nov., is erected for Paramenexenus yangi Chen & He, 2002 including the first descriptions of male and egg. One new species with two new subspecies, Marmessoidea hainanensis hainanensis sp. nov. & subsp. nov. and M. h. yinggelingensis subsp. nov., are described. Three combinations are suggested for Pseudoparamenexenus yangi (Chen & He, 2002) comb. nov. from Paramenexenus Redtenbacher, 1908; Asceles bidentatus (Chen & He, 2008) comb. nov. and Scionecra pseudocerca (Chen & He, 2008) comb. nov. from Aruanoidea Brunner von Wattenwyl, 1893 (= Necroscia Audinet-Serville, 1838). Asceles diadema Redtenbacher, 1908, is reported for the first time from China. Three species are first recorded in Hainan including Necroscia multicolor (Redtenbacher, 1908), Necroscia shukayi (Bi, Zhang & Lau, 2001) and Sipyloidea biplagiata Redtenbacher, 1908.